Intraspecies variation offers potential to improve white rot fungi for increasing degradability of lignocellulose for ruminants - Sonnenberg, Anton S. M.; Nayan, Nazri; Cone, John W.; van Peer, Arend F. (Multidisciplinary Digital Publishing Institute, 2024)
The aim of fungal treatment of organic matter for ruminants is the improvement of its degradability. So far, such treatment appears to be time-consuming and improvement has been modest. In previous work, we observed within three white rot species that there is modest (Ceriporiopsis subvermispora) or low (Lentinula edodes and Pleurotus eryngii) variation in fiber degradation in wheat straw during seven weeks of incubation. By extending and re-examining the data from all three species, we see that strains of C. subvermispora show the largest variation and improvement in the degradability of treated wheat straw. In addition, C. subvermispora also generated the highest absolute amount of degradable organic matter, a parameter not calculated before, but is very relevant for the economic feasibility of fungal treatment. In estimating fungal growth, we found no good correlation between an increase in ergosterol and a decrease in plant biomass, indicating a variation within fungal species of the ergosterol/fungal biomass ratio and/or a variation in carbon use efficiency, which has also not been analyzed before. This work contributes to the knowledge of how fungi degrade lignocellulose and further specifies what can be targeted for breeding to make fungal pretreatment economically feasible for upgrading organic waste streams into ruminal feed.